Characteristics of “Tip-DCs and MDSCs” and Their Potential Role in Leishmaniasis - Schmid, Maximilian; Wege, Anja K.; Ritter, Uwe (Frontiers in Microbiology, 2012)
Since the first description of dendritic cells (DCs) by Steinman and Cohn (1973), the myeloid lineage of leukocytes was investigated intensively. Nowadays it is obvious that myeloid cells, especially DCs, are crucial for the adaptive and innate immune response against intracellular pathogens such as Leishmania major parasites. Based on the overlapping expression of molecules that were commonly used to classify myeloid cells, it becomes difficult to denominate those cell types precisely. Of note, most of these markers used for myeloid cell identification are expressed on a broad range of myeloid cells, and should therefore be handled with care if used for subtyping of myeloid cells. In this mini-review we aim to discuss the relative impact of DCs that release TNF and nitric oxide (Tip-DCs) and myeloid cells with suppressive capacities (myeloid-derived suppressor cells, MDSCs) in infectious diseases such as experimental leishmaniasis. In our point of view it cannot be excluded that the novel subsets that were denominated as “Tip-DCs” and “MDSCs” might not be classical “subsets” but rather represent myeloid cells in a transient maturation stage expressing different genes, in response to the surrounding environment.